Intercropping chilli with maize or brinjal to suppress populations of Aphis gossypii Glov., and transmission of chilli viruses - Hussein, M.Y.; Abdul Samad, N. (Taylor & Francis Group, 1993)
A 2‐year field trial was conducted to evaluate the effectiveness of intercropping in suppressing Aphis gossypii a vector of chilli veinal mottle virus (CVMV) which causes severe damage to chilli plants (Capsicum annuum). One monocrop (chilli only) and two dicrops (chilli and maize, or chilli and brinjal) treatments were tested. No insecticides or fungicides were applied but pre‐emergence weedicides and other normal cultural practices were applied as recommended. The parameters used to compare the treatments were vector abundance, virus infection, plant height and fruit yield. The results showed that populations of A. gossypii found on the chilli plants were significantly (P < 0.05) larger in plots where chilli were grown as monocrop rather than as dicrops. Brinjal (Solanum melongena) seemed to perform better than maize (Zea mays) as a companion crop in protecting chilli plants from vector colonization and virus infection. Plant density appeared to have an influence on the vector abundance and virus spread as resources were limited, thus hampering vector movements in the intercropping system. Overall, CVMV infection was higher as the virus spread faster in chilli monoculture than dicultures involving either maize or brinjal. Trap catches of winged (alate) vectors also indicate that the vectors were more abundant and actively spreading the disease in the monocrop. No significant (P > 0.05) decrease or increase in the heights of chilli plants grown in the dicropping system was detected. Yields of fresh and marketable chillies were signifiantly higher when chilli plants were interplanted with either maize or brinjal. Brinjal was found to be the better companion crop, while maize could be used as a substitute. Brinjal was effective as a trap crop for those vectors migrating early, and also in diluting the vector population. Maize, on the other hand, acted as a barrier crop and was effective in reducing vector movement within a plot and also preventing winged vectors from landing on chilli plants. The study has demonstrated that a change in the cropping pattern or vegetational diversity could change the vector abundance and distribution while reducing virus transmission and spread.